BEBERAPA TIPE LICHEN PLANUS ORAL YANG DIPICU OLEH RAMIPRIL DAN STRES EMOSIONAL (Laporan kasus) - Anandina Irmagita; Gus Permana Subita (Faculty of Dentistry, Universitas Indonesia, 2015)
Lichen Planus is a chronic inflammatory disease that affects the skin and mucous membrane of squamous cell origin. Oral lichen Planus can occur without the skin lesion and there are six types of the oral lesion, erosive, atrophic, bulla, papular, plaque like and reticular. This disease can be caused by several factor, among them are antihypertensive drugs and emotional stress. In this case report we present a 43 years old female patient who suffered from several types of oral lichen planus that induced by ramipril, an antihypertensive drug, and emotional stress. There were some progressions after the drug was discontinued but the disease was worsening when emotional stress occurred. The severity of the disease can be controlled by the use of topical corticosteroid and multivitamin.